KAOLINITE MODIFIED BY ALUMINUM IN THE CRACKING OF VACUUM GASOIL AND IT’S MIXTURE WITH FUEL OIL - L.D. Volkova1; Zakarina N.N; Kim O.K; Akurpekova A.K; Zhumadullaev D.A; Yaskevich V.I; Grigorjeva V.P; Gabdrakipov A.V. (Academic Scientific Journal of Chemistry, 2020)
The data of the cracking of vacuum gas oil (VG) and a mixture of VG with fuel oil (M-100) on HLaY zeolite catalyst based on acid-activated kaolinite of the Pavlodar deposit modified by aluminum are presented. The synthesis of the kaolinite matrix and the HLaY zeolite catalyst with its use, the physicochemical and acid characteristics of the catalyst and its constituent components, and the fractional and hydrocarbon compositions of vacuum gas oil are described. High mesoporosity of the H-form of the used kaolinite (86.2%), modified by aluminum of the H-form (84.1) and the HLaY catalyst (80.1%), which provide the activity of the sample in cracking of the mixture with a yield of 32.6% gasoline and 25.9% light gas oil (LG) at 4500 С and in cracking of VG a yield of 38.2% gasoline and 29.4% LG at 5000 С. The gasolines of cracking of LG contain an increased content of iso paraffins (up to 20.2%) and a low content of aromatic hydrocarbons (24.1%), which makes the catalyst attractive for cracking a mixture of VG with fuel oil